The laureate [videorecording (DVD)] - Hughes, Tom, 1986-; Agron, Dianna, 1986-; Haddock, Laura, 1985-; Fee, Fra, 1987-; Glover, Julian, 1935-; Hodge, Patricia, 1946-; Anholt, Christien; Massachi, David (Gravitas Ventures, 2022)
Set in the mid-1920s, celebrated poet and writer Robert Graves returns from war traumatized and creatively struggling. It takes young poet Laura Riding to re-ignite Robert's passion, and with the blessing of his wife, Nancy, his muse becomes his lover. With the three of them sharing a life, soon, Laura's attention turns to Nancy, and a complicated relationship that scandalized society threatens to risk everything they have.